UCA1 Inhibits NKG2D-mediated Cytotoxicity of NK Cells to Breast Cancer - Yin, Jun-Yi; Zhou, Yao; Ding, Xiao-Ming; Gong, Run-Ze; Zhou, Yan; Hu, Hai-Yan; Liu, Yuan; Lv, Xiao-Bin; Zhang, Bing (Current Cancer Drug Targets, 2024)
Background: Natural killer cells play important roles in tumor immune surveillance, and cancer cells must resist this surveillance in order to progress and metastasise. Introduction: The study aimed to explore the mechanism of how breast cancer cells become resistant to the cytotoxicity of NK cells. Methods: We established NK-resistant breast cancer cells by exposing MDA-MB-231 cells and MCF-7 cells to NK92 cells. Profiles of lncRNA were compared between the NK-resistant and parental cell lines. Primary NK cells were isolated by MACS, and the NK attacking effect was tested by non-radioactive cytotoxicity. The change in lncRNAs was analyzed by Gene-chip. The interaction between lncRNA and miRNA was displayed by Luciferase assay. The regulation of the gene was verified by QRT-PCR and WB. The clinical indicators were detected by ISH, IH, and ELISA, respectively. Results: UCA1 was found to be significantly up-regulated in both NK-resistant cell lines, and we confirmed such up-regulation on its own to be sufficient to render parental cell lines resistant to NK92 cells. We found that UCA1 up-regulated ULBP2 via the transcription factor CREB1, while it up-regulated ADAM17 by “sponging” the miR-26b-5p. ADAM17 facilitated the shedding of soluble ULBP2 from the surface of breast cancer cells, rendering them resistant to killing by NK cells. UCA1, ADAM17, and ULBP2 were found to be expressed at higher levels in bone metastases of breast cancer than in primary tumors. Conclusion: Our data strongly suggest that UCA1 up-regulates ULBP2 expression and shedding, rendering breast cancer cells resistant to killing by NK cells.
Keywords: sULBP2